Pelatihan Deteksi Dini Karies Dalam Upaya Meningkatkan Pengetahuan Orang Tua dalam Menjaga Kesehatan Gigi Anak di Paud Gedawang Banyumanik Semarang - Wahyu Jati Dyah Utami; Supriyana Supriyana; Yodong Yodong (Jurnal Kesehatan Gigi, 2020)
The role and parents in fulfilling children's basic needs are the responsibility of the family, children's behaviour towards dental hygiene is influenced by the role of parents. When paying attention and caring about children's dental health, children will feel comfortable with the support of their parents. Parents' knowledge and skills can be improved by training. Several studies stated that counselling and training for health cadres gave effective results in increasing knowledge, attitudes and actions. Objective To determine the effect of early caries detection training on the knowledge and skills of parents in maintaining children's dental health at Paud Lentera Bunda Gedawang Post. This type of research is quantitative with a quasi-experimental research design with a one-group pretest-posttest design approach. The subjects of this study were the parents of 25 students of Pos Paud Lentera Bunda. The instrument used in this study was a questionnaire. Data analysis by calculating the frequency distribution and Wilcoxon Test statistical test with the help of the SPSS program. The level of parental knowledge before being given training with an average of 58.5, after being given training increased to 81.5. The results of statistical tests using Wilcoxon get a P-value of 0.000, which means p0.05. Based on the results of the study, 17% of children had caries signs with black colour, 14% white spots, 19% brown teeth, 25% had cavities and 22% healthy teeth. Early detection training is effective in increasing parental knowledge and skills in maintaining children's dental healthKeywords: Early Detection of Caries; Knowledge; Children